2008
DOI: 10.1007/s10554-008-9334-0
|View full text |Cite
|
Sign up to set email alerts
|

Lower patent foramen ovale detection with transthoracic echocardiography in atrial fibrillation

Abstract: This study is the first to demonstrate an apparent lower rate of PFO in patients with AF, using bubble contrast echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…This finding was similar to that of Attaran et al [3]. We believe that there are three reasons to explain this low rate of RLS detection in AF patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding was similar to that of Attaran et al [3]. We believe that there are three reasons to explain this low rate of RLS detection in AF patients.…”
Section: Discussionsupporting
confidence: 92%
“…Men comprised 52% of the AF group and 64% of the control group (p = 0.028). NIHSS score was higher in the AF group than in the control group (11 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] vs. 4 [2][3][4][5][6][7][8][9][10][11] In patients with AF, background and clinical characteristics of the RLS and non-RLS group are shown in Table 1. Past history of ischemic stroke was slightly more common in the RLS group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower risk of AF in patients with PFO compared with those without is consistent with the general view that patients with PFO are not at an increased risk of arrhythmias compared with the general population (31). In addition, studies have also demonstrated that the presence of AF reduces the likelihood of right-to-left shunting through the PFO due to the elevation of left atrial pressure and the change in the pressure gradient across the PFO (32,33). This in turn reduces the likelihood of PFO and AF co-detection.…”
Section: Discussionsupporting
confidence: 79%
“…This is because right atrial pressures may never exceed left atrial pressures, even in the presence of Valsalva augmentation. 48,95 Increased inferior vena cava flow may disrupt right atrial opacification, resulting in a false-negative bubble result. 35 In this scenario, blood flow through the inferior vena cava may be diminished by pressing firmly on the liver.…”
Section: False Negativesmentioning
confidence: 99%